Ultralong TE In Vivo 1 H MR Spectroscopy of Omega-3 Fatty Acids in Subcutaneous Adipose Tissue at 7 T - Gajdošík, Martin; Hingerl, Lukas; Škoch, Antonín; Freudenthaler, Angelika; Krumpolec, Patrik; Ukropec, Jozef; Ukropcová, Barbara; Šedivý, Petr; Hájek, Milan; Itariu, Bianca K; Maier, Bernhard; Baumgartner-Parzer, Sabina; et al. (Journal of magnetic resonance imaging, 2019)
BACKGROUND: Omega-3 (n-3) fatty acids (FA) play and important role in neural development and other metabolic diseases such as obesity and diabetes. The knowledge about the in vivo content and distribution of n-3 FA in human body tissues is not well established and the standard quantification of FA is invasive and costly. PURPOSE: To detect omega-3 (n-3 CH3 ) and non-omega-3 (CH3 ) methyl group resonance lines with echo times up to 1200 msec, in oils, for the assessment of n-3 FA content, and the n-3 FA fraction in adipose tissue in vivo. STUDY TYPE: Prospective technical development. POPULATION: Three oils with different n-3 FA content and 24 healthy subjects. FIELD STRENGTH/SEQUENCE: Single-voxel MR spectroscopy (SVS) with a point-resolved spectroscopy (PRESS) sequence with an echo time (TE) of 1000 msec at 7 T. ASSESSMENT: Knowledge about the J-coupling evolution of both CH3 resonances was used for the optimal detection of the n-3 CH3 resonance line at a TE of 1000 msec. The accuracy of the method in oils and in vivo was validated from a biopsy sample with gas chromatography analysis. STATISTICAL TESTS: SVS data were compared to gas chromatography with the Pearson correlation coefficient. RESULTS: T2 relaxation times in oils were assessed as follows: CH2 , 65 ± 22 msec; CH3 , 325 ± 7 msec; and n-3 CH3 , 628 ± 34 msec. The n-3 FA fractions from oil phantom experiments (n = 3) were in agreement with chromatography analysis and the comparison of in vivo obtained data with the results of chromatography analysis (n = 5) yielded a significant correlation (P = 0.029). DATA CONCLUSION: PRESS with ultralong-TE can detect and quantify the n-3 CH3 signal in vivo at 7 T. LEVEL OF EVIDENCE: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;50:71-82.
Keywords: lidé; Middle Aged; Adult; Fatty Acids, Omega-3; T2 relaxation; Phantoms, Imaging; omega-3 mastné kyseliny; prospektivní studie; n-3 fatty acids; Female; Gas Chromatography-Mass Spectrometry; Healthy Volunteers; fantomy radiodiagnostické; Computer Simulation; Humans; podkožní tuk; plynová chromatografie s hmotnostně spektrometrickou detekcí; Prospective Studies; Magnetic Resonance Spectroscopy; in vivo MRS; Subcutaneous Fat; long TE; lidé středního věku; Signal-To-Noise Ratio; poměr signál - šum; mužské pohlaví; 7 T; počítačová simulace; ženské pohlaví; Male; Aged; magnetická rezonanční spektroskopie; dospělí; zdraví dobrovolníci pro lékařské studie; senioři